Analisis Pengaruh Trust dan Halal Certification Terhadap Perilaku Niat Pembelian Ulang pada Makanan Halal Impor di Indonesia - Syaefulloh, Syaefulloh; Ramadhan, Hidayat, M. Rizki (Syntax Literate, 2026)
The increase in imported halal food consumption in Indonesia requires a more comprehensive understanding of the factors that influence consumer behavior in the economic and business contexts, especially repurchase intention. In the midst of increasing Muslim consumer awareness of the halal aspects of products, trust and halal certification are strategic determinants in building the sustainability of the relationship between consumers and products. This study aims to analyze the influence of trust and halal certification on the behavior of repurchase intentions on imported halal food in Indonesia, both partially and simultaneously. This study uses a quantitative approach with an explanatory research design. Data was collected through the distribution of questionnaires to 140 consumers of imported halal food in Indonesia who were selected using a non-probability sampling technique using the snowball sampling method. Data analysis was carried out using multiple linear regression supported by validity tests, reliability tests, and classical assumption tests. The results showed that halal certification and trust had a positive and significant effect on repurchase intention, both individually and simultaneously, with the model's ability to explain the variation in repurchase intention of 75.4%. These findings confirm that halal certification guarantees and consumer trust levels have an important role in encouraging the sustainability of imported halal food purchases. This research provides a theoretical contribution to the development of halal consumer behavior studies as well as practical contributions for business actors and policymakers in designing marketing strategies oriented towards strengthening trust and certainty of halal products.